Three new species of Camillina Berland, 1919 (Araneae: Gnaphosidae) from Brazil - Xavier, Cláudia; Ott, Ricardo; Saturnino, Regiane (Zootaxa, 2020)
The genus Camillina Berland, 1919 includes 75 valid species which are mainly distributed in South America. However, in Brazil, the knowledge regarding Camillina remains limited and a few contributions to the taxonomy of the genus have been made in the last two decades. Camillina belongs to Zelotinae, a group of gnaphosid spiders which diagnostic character is a preening comb on metatarsi III and IV, and the genus can be recognized by the presence of a prolaterally situated, bifid terminal apophysis and medially situated, recessed embolar base on the male palp and a median epigynal plate. Here, we describe the males and females of three new species: C. suya sp. nov. and C. kuarup sp. nov., both from Fazenda Tanguro, Querência, state of Mato Grosso, Brazil and C. bonaldoi sp. nov. from Parque Nacional de Sete Cidades, Piracuruca, state of Piauí, Brazil.